Cases in marketing management and strategy : an Asia-Pacific perspective - Quelch, John A.; Leong, Siew Meng; Ang, Swee Hoon; Tan, Chin Tiong (New York : Prentice Hall, 1996)
Business
1999-03-16
Keywords: Market management; Market planning